3 - The Informalization of Belonging: Igbo Informal Enterprise and National Cohesion from Below: https://doi.org/10.4314/ad.v34i1.57355 - Meagher, Kate (Africa Development, 2009)
The Nigerian Civil War evokes images of ethno-regional strife followed by sim- mering ethnic tension. However, political perspectives on the legacies of Biafra tend to gloss over the more integrative and constructive economic effects of the Civil War and its aftermath. While the Nigerian Civil War devastated Igbo busi- ness activities across Nigeria, and precipitated a mass return of Igbo migrants to their home area, it also laid the foundation for a consolidation and rapid devel- opment of Igbo informal enterprise, which has had integrative rather than divi- sive social and economic consequences for Nigeria as a whole. Operating below the radar of political competition, the demands of informal enterprise develop- ment have nurtured strong inter-ethnic and inter-regional links between the Igbo, Hausa, Yoruba and other Nigerian as well as non-Nigerian groups. With a particular focus on Igbo informal manufacturing, long-distance trading networks and informal money changing, this paper will consider the role of the informal economy in the development of popular structures of national unity. It will also show that these processes of economic integration from below have increas- ingly been strained by political struggles from above, creating a tide of violence and ethnic polarization that, even more than the Civi War, threatens to unravel the underlying social fabric of Nigerian nationhood.